The C‐terminal extension of human RTEL1, mutated in Hoyeraal‐Hreidarsson syndrome, contains Harmonin‐N‐like domains. Issue 6 (22nd November 2013) - Faure, Guilhem; Revy, Patrick; Schertzer, Michael; Londono‐Vallejo, Arturo; Callebaut, Isabelle
ABSTRACT Several studies have recently shown that germline mutations in RTEL1, an essential DNA helicase involved in telomere regulation and DNA repair, cause Hoyeraal‐Hreidarsson syndrome (HHS), a severe form of dyskeratosis congenita. Using original new softwares, facilitating the delineation of the different domains of the protein and the identification of remote relationships for orphan domains, we outline here that the C‐terminal extension of RTEL1, downstream of its catalytic domain and including several HHS‐associated mutations, contains a yet unidentified tandem of harmonin‐N‐like domains, which may serve as a hub for partner interaction. This finding highlights the potential critical role of this region for the function of RTEL1 and gives insights into the impact that the identified mutations would have on the structure and function of these domains. Proteins 2014; 82:897–903. © 2013 Wiley Periodicals, Inc.